Chabacano Legends: A Reflection of Zamboangueño’s Faith - Reyes, Aubrey F (International Journal of Membrane Science and Technology, 2023)
The primary goal of this study is to recognize, examine, and comprehend the Zamboangueños' religious beliefs as they are portrayed in the Chabacano stories of Zamboanga City. The stories of fifteen (15) written legends taken from Teresita P. Semorlan's "Chabacano Legends" and Orlando B. Cuartocruz's "Zamboanga Chabacano Folk Literature" (1990) were analyzed using historical and sociological precedent (1984). According to the study's findings, there are seven different types of religious belief held by Zamboangueños, including historical and traditional religion, unwavering faith, common or human faith, strong faith, rooted faith, active faith, and belief in miracles or apparitions. To completely capture and comprehend the meaning and interpretation of various faiths, the researcher spoke with several locals. It was determined that Zamboangueños, irrespective of their religion, have unwavering confidence in God.